The Effect of Giving Citric Acid with Different Concentration on The Level of Heavy Metal Lead (Pb) in Meat Green Mussel (Perna viridis) - Ernawati Ernawati; Nina Nurmalia Dewi; Juni Triastuti (Universitas Airlangga, 2022)
Green mussel (Perna viridis) is a fishery food that is often consumed by the community because the price is relatively affordable. This animal has the potential to be used because it has a large population, but one of the problems in Indonesian waters, especially Kenjeran Beach, is that it contains Pb metal. Consuming green mussels with Pb levels will interfere with body health, so it is necessary to take action to reduce the Pb metal content in green mussels, one of which is using citric acid. The purpose of this study was to determine the effect of soaking green mussel meat in citric acid with different concentrations on the reduction of Pb heavy metal levels. This research is a laboratory experimental with a Completely Randomized Design (CRD) consisting of 4 different treatments of immersion concentration in citric acid (0 , 0.21 , 0.25 and 0.29 M). The results showed that the immersion of green mussel meat in citric acid with concentrations of 0.21 , 0.25 and 0.29 M had a significant effect on the reduction of heavy metal lead (Pb) after immersion in citric acid at a concentration of 0.29 M is 0.1120 ppm, 0.25 M is 0.1167 ppm and 0.21 M is 0.1160 ppm. Soaking green mussels in citric acid with different concentrations did not affect the yield value of green mussel meat.